Kajian Kriminologi Penyalagunaan Narkotika oleh Anak di Kota Ternate - Rudi Hamdja; Tri Syafari; Anshar Anshar (Faculty of Law, Khairun University, 2020)
Abuse of narcotics by children in Ternate City actually occurs and is used by children who are still minors, either the child is a user / user or the child is a dealer, if it is categorized as narcotics abuse by children in Ternate City then the most dominating the category is a child as a user or a user who is a victim. The legal area of the North Maluku Regional Police and its staff in Ternate City is often found by children as drug users / users who are victims, in 2017 there were 2 cases of children who were netted with drug cases, in 2018 there were 1 cases of children and in 2019 there were 3 cases of children as users drugs, from these figures it shows that in the jurisdiction of the North Maluku Regional Police and the number of crimes of trafficking of Narcotics by minors still occurs, from a number of reasons children use or use narcotics because they are influenced by invitations from friends, curiosity or trial and error. try, the influence of the older siblings who live in, then the family is not harmonious and the environment in which they live.